Intragastric Balloon Therapy: Short-Term Gains and the Quest for Long-Term Success - Özden, Yavuz (Turkish Journal of Gastroenterology, 2026)
Cite this article as: Özden Y. Intragastric balloon therapy: short-term gains and the quest for long-term success. Turk J Gastroenterol. Published online February 23, 2026. doi: 10.5152/tjg.2026.25783.